Feasibility and Safety of Continuous and Chronic Bilateral Deep Brain Stimulation of the Medial Forebrain Bundle in the Naïve Sprague-Dawley Rat - Luciano L. Furlanetti; Máté D. Döbrössy; Iñigo A. Aranda; Volker A. Coenen (Behavioural Neurology)
Objective. Deep brain stimulation (DBS) of the superolateral branch of the medial forebrain bundle (MFB) has provided rapid and dramatic reduction of depressive symptoms in a clinical trial. Early intracranial self-stimulation experiments of the MFB suggested detrimental side effects on the animals’ health; therefore, the current study looked at the viability of chronic and continuous MFB-DBS in rodents, with particular attention given to welfare issues and identification of stimulated pathways. Methods. Sprague-Dawley female rats were submitted to stereotactic microelectrode implantation into the MFB. Chronic continuous DBS was applied for 3–6 weeks. Welfare monitoring and behavior changes were assessed. Postmortem histological analysis of c-fos protein expression was carried out. Results. MFB-DBS resulted in mild and temporary weight loss in the animals, which was regained even with continuing stimulation. MFB-DBS led to increased and long-lasting c-fos expression in target regions of the mesolimbic/mesocortical system. Conclusions. Bilateral continuous chronic MFB-DBS is feasible, safe, and without impact on the rodent’s health. MFB-DBS results in temporary increase in exploration, which could explain the initial weight loss, and does not produce any apparent behavioral abnormalities. This platform represents a powerful tool for further preclinical investigation of the MFB stimulation in the treatment of depression.